2020
DOI: 10.1186/s12943-020-01290-7
|View full text |Cite
|
Sign up to set email alerts
|

The complex relationship between MITF and the immune system: a Melanoma ImmunoTherapy (response) Factor?

Abstract: The clinical benefit of immune checkpoint inhibitory therapy (ICT) in advanced melanomas is limited by primary and acquired resistance. The molecular determinants of the resistance have been extensively studied, but these discoveries have not yet been translated into therapeutic benefits. As such, a paradigm shift in melanoma treatment, to surmount the therapeutic impasses linked to the resistance, is an important ongoing challenge.This review outlines the multifaceted interplay between microphthalmia-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 151 publications
1
36
0
Order By: Relevance
“…MITF is recognized as a major regulator of melanoma progression, but it can regulate multiple biological processes in melanoma cells, such as suppression of metastasis, differentiation, proliferation, migration, and senescence [ 36 ]. The increased MITF expression is associated with melanoma differentiation and proliferation, whereas decreased MITF expression is associated with a melanoma dedifferentiation [ 37 ]. The present study shows that PA downregulated MITF expression.…”
Section: Discussionmentioning
confidence: 99%
“…MITF is recognized as a major regulator of melanoma progression, but it can regulate multiple biological processes in melanoma cells, such as suppression of metastasis, differentiation, proliferation, migration, and senescence [ 36 ]. The increased MITF expression is associated with melanoma differentiation and proliferation, whereas decreased MITF expression is associated with a melanoma dedifferentiation [ 37 ]. The present study shows that PA downregulated MITF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 324,635 incident cases and 57,043 related deaths were reported worldwide in 2020 ( 1 ). In the past decades, immune checkpoint inhibitor therapy targeting cytotoxic T-lymphocyte antigen 4 (CTLA-4), programmed cell death receptor 1 (PD-1), and programmed cell death ligand 1 (PD-L1) have resulted in impressive outcomes in patients with malignant melanoma ( 2 ). However, approximately 40–65% of melanoma patients have no response to or develop relapse after anti-PD-1 therapy due to primary or acquired resistance, and over 70% of patients experience anti-CTLA-4 treatment failure ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…This signature is mainly composed of genes involved in EMT (such as AXL TWIST2), immunosuppressive genes (CCL2, CCL8) and interestingly, a number of genes that are regulated by MITF, the master regulator of melanocyte differentiation that is also implicated in melanoma migration, survival and stemness. This aspect is developed in [ 148 ].…”
Section: Therapeutic Strategies Targeting Immune Checkpointsmentioning
confidence: 99%
“…One protein that is critical to the phenotypic plasticity and resistance mechanisms in melanoma is the transcription factor MITF, the master regulator of melanocyte homeostasis [ 157 , 158 , 159 ]. Furthermore, MITF impacts immune function [ 148 ]. Interestingly, we recently showed that MITF controls the expression of ITGBL1.…”
Section: Resistance To Pd-1 Blockade Itgbl1 a New Immune Checkpoint?mentioning
confidence: 99%